The evolution in perception of journalism history in the works of English and American researchers - V.M. Vinichenko (Ученые записки Казанского университета: Серия Гуманитарные науки)
The aim of this paper is to trace the development of journalism history as an independent subfield in English and American historiography beginning with its spring from the sphere of book printing. Comparing the pioneering works of Anglo-American authors of the 19th century with those of their followers, the evolution of journalism history has been traced through the phases of formation, natural and social histories, and cultural history. The phase of formation was marked by the emergence of such groundbreaking works as those of A. Andrews in England and F. Hudson in the United States, who both treated the development of journalism as an inherent part of human history as a whole. The second phase starts with the opening of first Journalism Schools in the early 20th century. Contrary to their predecessors, the subsequent generation of historians believed that journalism and print media have their own “natural” history, which follows specific patterns. Having been manifested initially in two famous essays of R. Park and W. Lippmann, this approach was further developed in the well-known and still popular books of F.L. Mott, E. Emery, H.L. Smith, and others. However, during the second half of the 20th century, the “natural history approach” faced growing criticism for its limitations as well. This challenge should be answered by transition to the next phases of social and cultural histories. Finally, this paper underlines the importance of journalism history in overcoming the current journalism crisis, but journalism history in England and the United States should overcome its protracted staying in the phase of natural history to fulfill this purpose.